Differentiated instruction analysis on the topic of cell reproduction in 12th grade of senior high school - Fitri Husni Mardiyah; Rini Solihat (Assimilation: Indonesian Journal of Biology Education, 2023)
Differentiated instruction is learning that accommodates the diversity and differences in the characteristics of students. Therefore, teachers who teach in the classroom not only provide subject matter and value to students in the same way for all students in the class, but teachers need to pay attention to the diversity of students and provide services according to their needs. This study aims to determine the application of differentiated instruction in the classroom. The subjects of this study were teachers who taught grade XII on the topic of cell reproduction. This research is qualitative research with an explorative descriptive method. Data collection techniques in this study were interviews and assessment of teacher lesson plans. Primary data was obtained from the results of the analysis of lesson plans and the results of interviews with three teachers. Through this research, it was revealed that the teacher had implemented differentiation instruction, especially in cell reproduction material. However, not all teachers have implemented all aspects of differentiated instruction in content, process, and product.